Sport involvement and academic achievement : a study of Malaysian university athletes. - Chun, Cheng Chuan; Yusof, Aminuddin; Mohd Shah, Parilah (Canadian Center of Science and Education, 2013)
Factors that influence the academic achievement of Malaysian university athletes were investigated using 156 field hockey players from several universities. The relationship between team subculture, parental influence, the learning environment, support systems, financial aid, training factors, academic assistance, socialization, and stress level and academic achievements of student athletes were examined using the Team Socialization Scale (Allen, 1997). There was a significant positive relationship between the learning environment and academic achievements of university athletes but a negative relationship was found between support system and academic achievements. Implications and suggestions on how to improve the academic achievement of athletes in Malaysian universities were discussed in the study.